1995
DOI: 10.1002/ar.1092430303
|View full text |Cite
|
Sign up to set email alerts
|

Type VI collagen in mouse masseter tendon, from osseous attachment to myotendinous junction

Abstract: The distribution of type VI collagen in mouse masseter tendon is different in different anatomical position. This may reflect the different functional demand for this collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…It was speculated that Bethlem myopathy may also be caused by a disturbance of a type VI/laminin interaction (18), but our results (not shown) and those of others show that there is no interaction between type VI and laminin (49). However, type VI collagen is associated with the external lamina of muscle cells in the myotendinous junction (50), and this study demonstrates a co-distribution of type VI and type IV collagens in human skeletal muscle. These studies have demonstrated a direct protein/protein interaction of type VI collagen with basement membrane type IV collagen, indicating that type VI filaments provide a physical link between endothelial basement membranes and the surrounding matrix.…”
Section: Discussioncontrasting
confidence: 51%
“…It was speculated that Bethlem myopathy may also be caused by a disturbance of a type VI/laminin interaction (18), but our results (not shown) and those of others show that there is no interaction between type VI and laminin (49). However, type VI collagen is associated with the external lamina of muscle cells in the myotendinous junction (50), and this study demonstrates a co-distribution of type VI and type IV collagens in human skeletal muscle. These studies have demonstrated a direct protein/protein interaction of type VI collagen with basement membrane type IV collagen, indicating that type VI filaments provide a physical link between endothelial basement membranes and the surrounding matrix.…”
Section: Discussioncontrasting
confidence: 51%
“…This would suggest a disruption of the normal interconnecting meshwork between the cell and its pericellular matrix. While immunolocalization for Type VI collagen was not performed in the current study, previous investigations using electron microscopy have identified this loosely bound, fine, fibrillar material as Type VI collagen [43,51]. Additional studies are required to confirm that the material observed in our stress-deprived system is Type VI collagen.…”
Section: Discussionmentioning
confidence: 73%
“…Given its morphology and distribution in tendons, it has been attributed an integrative function, organizing collagen fibers and linking them to the cells (Bruns et al 1986). Type VI collagen has been found in the osseous attachment to the myotendinous junction of the masseter tendon (Senga et al 1995), and spatial interactions of type VI collagen, small proteoglycans, and collagen fibrils have been observed in tendons (Watanabe et al 1997). Nurminskaya and Birk (1998) have shown that type VI collagen is expressed after the fibrillogenesis phase.…”
Section: Introductionmentioning
confidence: 99%